Characteristic of oil palm empty fruit bunch pretreated with Pleurotus floridanus (Pretreatment biologi tandan kosong kelapa sawit menggunakan Pleurotus floridanus) - . ISROI (Menara Perkebunan, 2017)
Pleurotus floridanus have ability on lignin degradation by producing ligninolytic enzyme and prefer to degrade lignin than carbohydrate (hemicellulose and cellulose). Oil palm empty fruit bunches has been pretreated using P. floridanus.  Addition of cation (Cu2+) on biological pretreatment reduced lignin content and increased digestibility of the empty fruit bunches. P. floridanus reduce lignin and hemicellulose content from 23.9% to 10.1% and from 20.8% to 16.9%, respectively. P. floridanus did not degrade cellulose. Cellulose content of empty fruit bunches increase from 40.4% to 51.7%. Crystallinity of empty fruit bunches reduced after biological pretreatment. Crystallinity presented as LOI (lateral order index) of un-treated and biological pretreated oil palm empty fruit bunches are 2.08 and 1.44. Digestibility of the empty fruit bunches increased from 17.2% to 60.3% by biological pretreatment.[Key words:  biological pretreatment, oil palm empty fruit bunches, Pleurotus floridanus, biofuel, white-rot fungi, lignocellulose]AbstrakPleurotus floridanus memiliki kemampuan untuk mendegradasi lignin dengan memproduksi enzim ligninolitik dan lebih memilih untuk mendegradasi lignin daripada karbohidrat (hemiselulosa dan selulosa). Kemampuan unik P. floridanus ini dimanfaatkan dalam pretreatment biologi tandan kosong kelapa sawit. Penambahan kation (Cu2+) pada pretreatment biologi menurunkan kandungan lignin dan meningkatkan digestibiliti tandan kosong kelapa sawit. Perlakuan P. floridanus mengurangi kandungan lignin dan hemiselulosa dari 23,9% menjadi 10,1% dan dari 20,8% menjadi 16,9%. Perlakuan P. floridanus tidak menurunkan kandungan selulosa. Kandungan selulosa tandan kosong kelapa sawit meningkat dari 40,4% menjadi 51,7%. Kristalinitas tandan kosong menurun setelah pretreatment biologi. Kristalinitas yang dinyatakan dalam LOI (LOI, Lateral Order Index) adalah 2,08 untuk tandan kosong tanpa pretreatment biologi dan 1,44 untuk tandan kosong dengan pretreatment biologi. Digestibiliti itandan kosong meningkat dari 17,2% menjadi 60,3%.[Kata kunci: Pretreatment biologi, tandan kosong kelapa sawit, jamur pelapuk putih, lignoselulosa, Pleurotus floridanus]